2020
DOI: 10.1002/car.2627
|View full text |Cite
|
Sign up to set email alerts
|

What Do Confessions Reveal about Abusive Head Trauma? A Systematic Review

Abstract: Although confessions related to abusive head trauma (AHT) are reported, no detailed analysis exists. Therefore, we systematically reviewed studies of AHT confessions and examined the details, including country of origin, mechanisms and perpetrators' characteristics. Employing 36 search terms across three search engines, we searched Medline and CINAHL from 1963 to 2018. All relevant studies underwent two independent reviews and data extraction. Descriptive statistics were used to characterise the sample; chi sq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
55
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 29 publications
(58 citation statements)
references
References 60 publications
1
55
0
2
Order By: Relevance
“…Parental mental health impairment and psychiatric disorders have been identified as factors associated with child physical abuse, which might have resulted in an increase in female perpetrators during the lockdown. This may have had an influence on the gender ratio of perpetrators, considering that previous studies have shown that male perpetrators are responsible for 60–70% of child physical abuse cases ( Edwards et al, 2020 ; Starling & Holden, 2020 ). While the increased frequency of female perpetrators might potentially be associated with an altered gender ratio of physically abused children, the finding remains rather puzzling.…”
Section: Discussionmentioning
confidence: 99%
“…Parental mental health impairment and psychiatric disorders have been identified as factors associated with child physical abuse, which might have resulted in an increase in female perpetrators during the lockdown. This may have had an influence on the gender ratio of perpetrators, considering that previous studies have shown that male perpetrators are responsible for 60–70% of child physical abuse cases ( Edwards et al, 2020 ; Starling & Holden, 2020 ). While the increased frequency of female perpetrators might potentially be associated with an altered gender ratio of physically abused children, the finding remains rather puzzling.…”
Section: Discussionmentioning
confidence: 99%
“…None of these transcriptions reported that the infant had symptoms before this sudden occurrence of the LOC. This contrasts with further versions that these adults gave to police officers, where in some cases they mentioned symptoms prior to the LOC, reinforcing the frequent ‘changing history’ observed in cases of AHT (Edwards et al ., 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Although infants were described as not crying habitually in this study, one cannot rule out that crying increases in the presence of an abusive adult, and crying remains a trigger that is often mentioned in AHT occurrence (Edwards et al ., 2020). In any case, it is important to give a universal simple message about the fact that a child can cry for prolonged periods without being ill, and that a baby may be abused by an exasperated adult.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Accidental head injuries, resulting mostly from impact, and inflicted head injuries, resulting from either shaking or impact, or a combination of the two, overlap considerably (Christian, 2007; Kemp et al ., 2011). Confessions (Edwards et al ., 2020) and eyewitness accounts can help determine the mechanism of injury, but they can sometimes be false. Therefore, the determination of the mechanism of an inflicted head injury is often difficult.…”
mentioning
confidence: 99%